2020
DOI: 10.3390/plants9070877
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophytes Promote Tomato Growth and Enhance Drought and Salt Tolerance

Abstract: In a search for efficient fungal endophytes that can promote crop production and/or increase crop tolerance to abiotic stress, we isolated and tested various species harbored by wild plants. Sixty-seven endophytic fungal isolates were obtained from drought stressed, poor soil habitats, and inland high salt areas. We extensively tested the roles of Ampelomyces sp. and Penicillium sp. isolates in improving tomato growth and yield. Under greenhouse and field trails, Ampelomyces sp. and Penicillium sp. end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…The evaluation of the tolerance of fungal strains to the saline environment has received great attention in recent years [ 28 , 29 ]. Moreover, the tolerance of fungal endophytes to different hyper-saline concentrations of sodium chloride was reported by several recent studies [ 28 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the tolerance of fungal strains to the saline environment has received great attention in recent years [ 28 , 29 ]. Moreover, the tolerance of fungal endophytes to different hyper-saline concentrations of sodium chloride was reported by several recent studies [ 28 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endophytic fungi, Ampelomyces sp. or P. chrysogenum improved growth and drought and salinity stress tolerance in tomato (Morsy et al, 2020).…”
Section: Endophytic Fungi-mediated Salinity Stress Tolerancementioning
confidence: 96%
“…In the grass Brachypodium distachyon , drought stress was mitigated with the help of an endophytic bacterium Bacillus subtilis B26, which also upregulated the stress responsive genes [ 76 ]. Morsy et al [ 77 ] reported that the endophytic fungal strains Ampelomyces sp. and Penicillium sp., isolated from stress inducing soil (drought and high salinity), enhanced drought tolerance ( Ampelomyces sp.)…”
Section: Endophyte Mediated Drought and Salinity Stress Managementmentioning
confidence: 99%